Training on the Utilization of Word Processing Applications, Numbers and Presentation using Microsoft Office on Foundation Al Muhajirin Islamic Education and Welfare, Bogor City - Putie Maharani; Hilda Rachmi; Abdul Hamid; Rachmat Suryadithia (PT FORMOSA CENDEKIA GLOBAL, 2022)
Community Service is one of the Tri Dharma of higher education that must be carried out by lecturers. In this service, the lecturers from Bina Sarana Informatics University conducted training for the staff of the Al-Muhajirin Islamic Education Foundation in the city of Bogor. The training is in the form of word processing, numbers and presentations. Where foundation staff will be taught how to use Microsoft Office applications. For the method of carrying out this activity in the form of word processing training using Ms.Word, number processing using Ms. Excel and making report presentations using Ms. Power point. This training will be held on September 17 2022 at 09.00 until finished. With this training, it is hoped that the foundation's staff will be able to understand and be able to apply the use of Microsoft Office applications and take advantage of the features in these applications. The target of this community service activity is to help foundation staff by providing knowledge about the use of Microsoft Office applications. While the output targets to be produced are from this community service, namely: 1) Training Module for the Utilization of Word Processing Applications, Numbers and Presentations using Microsoft Office. 2) Articles in local print or electronic media. 3) Implementation documentation and 4) Journals published. media massa cetak atau elektronik lokal. 3)Dokumentasi pelaksanaan dan 4) Jurnal yangditerbitkan.